Sustainability Disclosure of GRI Towards Improving The Welfare of Local Communities in Shipping Industry Companies in Surabaya - Tumbelaka, Gracesheila Florencia; Ekasari, Kurnia; Wahyuni, Hesti (Journal of Applied Business, Taxation and Economics Research, 2024)
This research discusses and analyzes the Corporate Social Responsibility (CSR) programs implemented by PT PAL Indonesia (Persero) and PT Adiluhung Saranasegara Indonesia. Using a qualitative approach, this research explores the impact of CSR programs on improving the welfare of local communities. The data analysis method used is content analysis, with the research sample involving PT PAL Indonesia and PT Adiluhung Saranasegara Indonesia in Surabaya. The discussion covers aspects of education, economy, environment, and spiritual well-being. The results show that PT PAL Indonesia is holistically involved in supporting Micro, Small and Medium Enterprises (MSMEs) and the education sector with training and scholarship programs. Involvement in environmental activities and the construction of worship facilities also reflects the company's commitment to spiritual and environmental aspects. PT Adiluhung Saranasegara Indonesia, on the other hand, shows concern for health and social assistance, with the distribution of aid to vulnerable groups and victims of natural disasters. While both companies have not reported fully on GRI 300 (Environment) and GRI 400 (Social) standards, their positive contributions to the well-being of local communities remain significant. However, further steps are needed to increase transparency and comprehensiveness in CSR reporting in order to improve the effectiveness of the companies' CSR reporting.